Die Mallophagen von Sturmvögeln und Ruderfüßern. I. Harrisoniella Bedford und Perineus Thompson (Mallophaga) (2. Fortsetzung). - Kéler, Stefan von (Contributions to Entomology = Beiträge zur Entomologie, 1957)
The present 2d continuation of the paper (1st cont. see Beitr. Ent., 7, 281-297, 1957) brings the taxonomy of the genera Diomedicola n. gen. and Perineus Thompson, the first of them with one, the last with three new species. As it is the rule in the Authors papers, the taxonomic considerations are combined with some general morphological questions. The economy of space has vorbidden to discuss some illustrations of general importance, which may speak for themselves.Nomenclatural Actsirroratae Kéler, 1957 (Diomedicola), spec. n.Diomedicola Kéler, 1957 (Mallophaga), gen. n.Perineus Thompson, 1936 (Mallophaga), stat. rev. nec Perineus Harrison in Thompson, 1936circumfasciatus Kéler, 1957 (Perineus), spec. n.concinnoides Kéler, 1957 (Perineus), spec. n.oblongus Kéler, 1957 (Perineus), spec. n.